Periodontal Health and Caries Prevalence Evaluation in Patients Affected by Parkinson's Disease - Marco Cicciù; Giacomo Risitano; Giuseppe Lo Giudice; Ennio Bramanti (Parkinson's Disease)
Parkinson's disease (PD) is a progressive neurodegenerative disorder related to the loss or absence of dopaminergic neurons in the brain. These deficits result in slowness of movement, tremor, rigidity, and dysfunction of behaviour. These symptoms negatively influence the patient’s capability to carry out the daily oral hygiene manoeuvres. The aim of this work is to record the oral health condition of PD patients evaluated at the IRCSS Bonino-Puleio in Messina. The oral health of 45 consecutive PD patients (study group) with neurologic diagnosis based on United Kingdom Brain Bank Criteria has been compared with that of another 45 no PD patients of the same age (control group). The evaluation of the general oral condition was recorded underlining tooth loss, active periodontal disease, and presence of untreated caries. The frequency of untreated caries, periodontal diseases, and missing teeth of the study group was significantly higher than in control group. Based on the data results, clinicians should direct high attention to the oral hygiene of patients with PD, above all at the early stages of the caries or periodontal disease, in order to prevent serious evolution of those pathologic dental conditions that may finally result in the tooth extraction event.